2009
DOI: 10.1002/pmic.200800192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of elicitor‐responsive proteins in rice leaves by a proteomic approach

Abstract: Experiments were conducted to identify the differentially expressed proteins in rice (Oryza sativa L.) plants after treatment with the glycoprotein elicitor CSB I, purified from ZC(13), a race of the rice blast fungus Magnaporthe grisea. The interactions of two near isogenic lines of rice, C101A51 and CO39, with ZC(13) resulted in completely incompatible and compatible types, respectively. Proteins were extracted from rice leaves at 12 and 24 h after treatment with CSB I. Temporal changes in total proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 76 publications
2
33
0
1
Order By: Relevance
“…There is substantial prior evidence that NDPK-1 and NDPK-2 are upregulated during oxidative stress responses, as well as physically interact with catalases and stressrelated MAP kinases (Kovtun et al 2000;Sweetlove et al 2002;Fukamatsu et al 2003;Moon et al 2003;Kav et al 2004;Hajheidari et al 2005;Dooki et al 2006;Hammargren et al 2007b;Verslues et al 2007;Liao et al 2009;Haque et al 2010;Hasunuma et al 2011;Immel et al 2012). Moreover, NDPK-1 and NDPK-2 overexpression and knockout studies indicated a positive correlation between NDPK activity and stress tolerance (Fukamatsu et al 2003;Baek et al 2004;Yoshida et al 2006;Tang et al 2008;Kim et al 2009Kim et al , 2010Kim et al , 2011.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…There is substantial prior evidence that NDPK-1 and NDPK-2 are upregulated during oxidative stress responses, as well as physically interact with catalases and stressrelated MAP kinases (Kovtun et al 2000;Sweetlove et al 2002;Fukamatsu et al 2003;Moon et al 2003;Kav et al 2004;Hajheidari et al 2005;Dooki et al 2006;Hammargren et al 2007b;Verslues et al 2007;Liao et al 2009;Haque et al 2010;Hasunuma et al 2011;Immel et al 2012). Moreover, NDPK-1 and NDPK-2 overexpression and knockout studies indicated a positive correlation between NDPK activity and stress tolerance (Fukamatsu et al 2003;Baek et al 2004;Yoshida et al 2006;Tang et al 2008;Kim et al 2009Kim et al , 2010Kim et al , 2011.…”
Section: Figmentioning
confidence: 92%
“…One intriguing protein identified by this analysis, nucleoside diphosphate kinase-3 (NDPK-3), is a member of a small family known to be active in plant responses to external environmental cues, in addition to their canonical roles as nucleoside phosphotransferases (Hammargren et al 2007b). Upregulated NDPK protein levels have been detected after growing plants in high salinity (Kav et al 2004;Dooki et al 2006), in polluted soil containing a mixture of metals and PAHs (Immel et al 2012), in drought conditions (Hajheidari et al 2005), after treatment with pathogen elicitors (Liao et al 2009), and following the oxidative stress treatments of H 2 O 2 , menadione, and antimycin A (Sweetlove et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Four-leaf stage rice plant treated with CSB I was analyzed by the 2-DGE-based proteomics approaches (Liao et al 2009). A total of 18 protein spots were identified by LC-MS/MS and that included 11 upregulated and 7 newly synthesized protein spots.…”
Section: Elicitormentioning
confidence: 99%
“…Those biotic studies involve elicitor (Agrawal et al 2002;Chen et Y. Wang : K. Y. Kang al. 2007a;Lin et al 2008;Liao et al 2009), fungus (Kim et al 2003(Kim et al , 2004(Kim et al , 2009Lee et al 2006), bacterium (Mahmood et al 2006;Chen et al 2007b;Kandasamy et al 2009;Chi et al 2010), virus (Ventelon-Debout et al 2004), herbivore (Wei et al 2009), and mammalian (Fan et al 2011). In this review, we summarize proteomics studies of biotic stresses in rice.…”
Section: Introductionmentioning
confidence: 99%
“…The two proteins are classified as mannose-specific, jacalin-related lectins (Peumans et al 2000), and their gene transcripts are induced by salt and drought stresses and phytohormones such as JA or ABA treatment (Garcia et al 1998;Hirano et al 2000;Kim et al 2003;Moons et al 1997). Moreover, SalT expression was induced after inoculation with Magnaporthe oryzae and after treatment with a fungal elicitor (Kim et al 2003(Kim et al , 2004Liao et al 2009). Although the expression of MRL in response to infection with the rice blast fungus has not yet been characterized, these studies raise the possibility that MRL may function in a defensive reaction as well as SalT.…”
Section: Introductionmentioning
confidence: 97%